Alleviation of Trigeminal Nociception Using p75 Neurotrophin Receptor Targeted Lentiviral Interference Therapy - O'Leary, Valerie B.; O'Connell, Marie; Antyborzec, Inga; Ntziachristos, Vasilis; Dolly, J. Oliver; Ovsepian, Saak V. (Neurotherapeutics, 2018)
Acute and chronic trigeminal (TG) neuropathies are the cause of considerable distress, with limited treatments available at present. Nociceptive neurons enriched with the vanilloid type 1 receptor (VR1) partake in pain sensation and sensitization in the TG system. While VR1 blockers with anti-nociceptive potential are of substantial medical interest, their use remains limited due to poor selectivity and lack of cell-targeting capabilities. This study describes a methodology for the alleviation of nociception via targeted depletion of VR1 in TG sensory neurons in rats. In cultured TG ganglion neurons, VR1 expression was virtually abolished by lentiviral short hairpin RNA (LV-VR1). By decorating GFP encoding LV (LV-GFP) and LV-VR1 with IgG192 for targeting TG sensory neurons enriched with the p75 neurotrophin receptor (p75NTR), transduction of a reporter GFP and VR1 depletion was achieved after injection of targeted vectors into the whisker pad. In IgG192/LV-VR1-injected rats, the behavioral response to capsaicin exposure as well as Erk 1/2 phosphorylation and VR1 current activation by capsaicin were significantly reduced. This pioneering investigation, thus, provides a proof of principle for a means of attenuating TG nociception, revealing therapeutic potential.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Capsaicin; Neuropathic pain; Neurotherapeutics; p75NTR; TRPV1